LO57: Twitter as an educational tool for medical students in their emergency medicine rotation: a prospective cohort study. (May 2019) - Bruneau, V.; Paradis, M.; Lonergan, A.; Morris, J.; Piette, E.; Castonguay, V.; Paquet, J.; Cournoyer, A.
Abstract : Introduction : Different tools have been developed to complement medical training, and improve student learning. Although social media has been described as an innovative educational strategy, evidence for its use is scarce in emergency medicine (EM). The primary outcome of this study was to evaluate whether brief teaching points (tweets) sent to medical students (MS) via a Twitter feed, would yield better exam score at the end of an emergency medicine (EM) rotation.Methods : Participants included in this prospective cohort study were MS completing an EM rotation at our tertiary care academic center. The control group was recruited from December 2016 to November 2017 and the experimental group from November 2017 to November 2018. The MS in the experimental group were invited to follow a Twitter feed. A total of 32 EM-related tweets based on learning objectives were sent out throughout the 4 week rotation. At the end of the rotation, MS of both cohorts took an exam and completed a survey of assiduity and appreciation. Exam scores were compared using t-tests.Results : A total of 80 MS were recruited for the study, 38 in the experimental cohort. Average exam scores were similar in both cohorts (control = 63 ± 9% vs experimental = 64 ± 8% for a mean difference of -2% [95%CI -6 to 2], p = 0.37). Of the experimental group, only 7 (18%) of the participants reported viewing more than 50% of the tweets. There was no difference between mean exam scores of this sub-group and that of the control cohort (66 ± 10% for a mean difference of 4% [95%CI -4 to 11], p = 0.33). The majority (n = 20, 53%) of the MS in the experimental cohort did not read any tweets. When compared to the rest of the experimental cohort MS who reported viewing ≥50% of the tweets found the Twitter feed to be a useful educational tool. Indeed, on a 3 item Likert scale used to evaluate different aspects of appreciation, they found the Twitter feed to be beneficial to their rotation (86% vs 13%, p < 0.001) as well as helpful in patient management (71% vs 16%, p = 0.001). These same MS would have liked more tweets (100% vs 19%, p < 0.001) and would like to use Twitter in other rotations (100% vs 32%, p = 0.005).Conclusion : In this study, there was no difference in the exam scores between MS having access to regular EM-focused educational tweets in comparison to those who did not. Results also found a lower than expected assiduity of MS to the educational Twitter feed, although those who used it significantly found it useful.